POSTNATAL FOLLOW-UP AND OUTCOME OF INFANTS DIAGNOSED WITH ANTENATALLY DETECTED HYDRONEPHROSIS: AN OBSERVATIONAL STUDY - AKASH YADAV; SINDHU N; GAUTAM MUTHU (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objectives of this study were to evaluate the postnatal outcomes of neonates with antenatally detected hydronephrosis (ANH), to determine the prevalence of associated urinary tract anomalies such as pelviureteric junction obstruction (PUJO), vesicoureteral reflux (VUR), and posterior urethral valves (PUV), and to assess the requirement for surgical versus conservative management Methods: This prospective observational study included 60 neonates diagnosed with ANH based on antenatal ultrasound criteria (anteroposterior renal pelvic diameter >4 mm in the second trimester or >7 mm in the third). Postnatal evaluations included serial ultrasonography and, in selected cases, micturating cystourethrogram. Hydronephrosis was graded using the Society for Fetal Urology system. Primary outcomes included resolution rates, incidence of urinary tract anomalies, surgical intervention rates, and urinary tract infection occurrence. Data were analyzed using SPSS v23. p<0.05 was considered statistically significant. Results: Among 60 infants, 68.3% were male, with a male-to-female ratio of 2.2:1. Hydronephrosis was unilateral in 54 cases (90.0%) and most commonly left-sided. On initial postnatal ultrasound, 63.3% had mild, 25.0% moderate, and 11.7% severe hydronephrosis. Till the time of final follow-up, 44 (73.3%) cases resolved spontaneously without intervention. Specific pathologies identified were PUJO (11.7%), VUR (13.3%), and PUV (3.3%). Surgical intervention was required in 13.3% of infants. The reduction in hydronephrosis severity from antenatal to postnatal imaging was statistically significant (p<0.001). Conclusion: Most cases of ANH resolve without any interventions. Serial postnatal follow-up using ultrasonography is important for identifying infants at risk for the presence of clinically significant anomalies such as PUJ obstruction, VUR, and PUV. Regular follow-up facilitates timely intervention while avoiding unnecessary procedures in low-risk cases.